2021
DOI: 10.1161/jaha.120.020088
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Dipeptidyl Peptidase 4 Inhibition Worsens Hypertension and Renal and Cardiac Abnormalities in Obese Spontaneously Hypertensive Heart Failure Rats

Abstract: Background The long‐term effects of dipeptidyl peptidase 4 (DPP4) inhibitors on blood pressure and cardiovascular and renal health remain controversial. Herein, we investigated the extended (>182 days) effects of DPP4 inhibition in a model of spontaneous hypertension, heart failure, diabetes mellitus, obesity and hyperlipidemia. Methods and Results Adult obese spontaneously hypertensive heart failure rats (SHHF) were implanted with rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Moreover, DPP-4 inhibitors' long-term effects on blood pressure, cardiovascular, and renal health are still up for debate. It was suggested that long-term DPP4 inhibitor treatment may be harmful in certain genetic backgrounds and provide an animal model to investigate the mechanisms underlying DPP4 inhibitor-induced pathological conditions and test preventative measures [5].…”
Section: Short Communicationmentioning
confidence: 99%
“…Moreover, DPP-4 inhibitors' long-term effects on blood pressure, cardiovascular, and renal health are still up for debate. It was suggested that long-term DPP4 inhibitor treatment may be harmful in certain genetic backgrounds and provide an animal model to investigate the mechanisms underlying DPP4 inhibitor-induced pathological conditions and test preventative measures [5].…”
Section: Short Communicationmentioning
confidence: 99%